The Influencing Factors of Breastfeeding for Full-Term Singleton Within Six Months of Birth in Xi'an Before the Covid-19 Pandemic - Yuan, Zhan-Wang; Ma, Li; Ge, Wen-Li; Li, Xiao-Ying; Zhang, Xiao-Qin; Zeng, Jing-Jie; Yang, Jun; Qu, Peng-Fei (Frontiers in Pediatrics, 2022)
Objective To understand the situation of full-term infants breastfeeding within six months of birth in Xi’an before the Covid-19 pandemic and analyze the influencing factors of exclusive breastfeeding. Methods Five hospitals in Xi’an were selected as the research centers, and full-term infants who met the inclusion and exclusion criteria were recruited from January 1 to February 28, 2019. The feeding situation at 10 days, 42 days, 3 months, and 6 months after birth were investigated. A self-designed breastfeeding questionnaire was used for investigation and follow-up. SPSS 22.0 was applied for statistical analysis of the data. Results The exclusive breastfeeding rate of full-term infants on days 10 and 42 and at months three and six after birth was 61.39, 54.78, 48.83, and 38.78%, respectively, with a decreasing trend over time. During breastfeeding within 48 hours after delivery, 1,653 cases (91.83%) of puerpera had different grades of pain, including 1,325 cases (80.16%) of mild discomfort, 321 cases (19.42%) of moderate pain, and seven cases (0.42%) of severe pain. Within 24 to 48 hours postpartum, 1607 (89.27%) mothers faced problems related to postpartum breastfeeding. Among them, 694 (43,19%) neonates could not be fed effectively; 665 (41.38%) mothers had wound pain and had inconvenience to turn over; 598 (37.21%) neonates were difficult to wake up; 439 (27.32%) mothers had incorrect feeding posture; 181 (11.26%) mothers experienced other problems. The Cox risk regression model showed that weight gain during pregnancy was higher than the recommended standard. Living in suburban counties was a risk factor of exclusive breastfeeding for full-term infants. Participation in breastfeeding courses during pregnancy, feeding more than eight times daily after delivery, and proposed breastfeeding for 12 months or more were the protective factors of exclusive breastfeeding for full-term infants. Conclusion The body weight gain of parturients should be controlled within a reasonable range during pregnancy. Parturients were encouraged by medical staff to participate in breastfeeding courses or watch the breastfeeding process during pregnancy to increase their self-confidence and improve the rate of exclusive breastfeeding for full-term infants.